Study of earthquake waveforms from a new deployment of seismographic stations in northern Iraq - Ahmed, Omar Qadir; Aziz, Bakhtiar Qadir (Sulaimani Journal for Pure and Applied Sciences, 2013)
This study is to investigate four different body wave phases from events recorded by eight modern broad-band seismographic stations (NISN) installed in northeastern Iraq. From this network of stations which is distributed in Kurdistan region, a three-component digital data obtained that have been recorded continuously at a rate of 100 sps. The analyses include identifying the P- and S-wave phases from different azimuths and locating the events. The processed local and regional earthquakes which have been recorded in the studied area were in the close proximity to the northeastern border of the Arabian plate and occurred over a period between (2010-2012). In this study, the hypocentral depths are derived from the picked arrival times of P/Pg/Pn, S/Sg and Sn phases and a map was drawn which depicts the epicentral distances for the analyzed waveforms. Furthermore, the source magnitude has been calculated from the amplitude of the wave energy. The resulting events distribution reveals a distinct picture of the interaction between seismicity and seismotectonics of the region. The highest seismicity rate seems to be confined to the exceedingly active northern section of the Zagros thrust zone.
Keywords: Body waves; amplitude; broadband filter; detection and traveltime